"He's just a baby": Forensic interviewers' experiences and perceptions of maltreated preschoolers' participation in the criminal justice system. (March 2020) - Katz, Carmit; Kosher, Hanita
Highlights: 3 barriers prevent preschoolers from participation in the justice system. Forensic interviewers feel guidelines are inadequate to preschoolers. The criminal justice system does not allow preschooler participation. Policy change is essential. Abstract: In many countries throughout the world, children are required to come face to face with the criminal justice system following suspected abuse. This encounter is challenging regardless of their age, but particularly so for preschoolers. The current study examined how forensic interviewers – acting in the Israeli context as frontline practitioners in the process of maltreated children's participation in the criminal justice system – experience and perceive maltreated preschoolers' participation. Nine focus groups were held with a total of 90 forensic interviewers, and thematic analysis was applied to their narratives. The participants identified three major barriers for preschoolers' participation: developmental capabilities, the interviewers' emotional barriers when interacting with young children in the aftermath of suspected maltreatment, and the criminal justice system, which in its current form is not conducive to the participation of maltreated preschoolers. The discussion addresses the urgent need to modify the criminal justice system in order to better promote preschoolers' participation.